Typhlotanais plicatus : Kudinova-Pasternak 1993 - Błażewicz-Paszkowycz, Magdalena (Zenodo, 2007)
Typhlotanais plicatus Kudinova-Pasternak, 1993 (Fig. 77) Typhlotanais plicatus : Kudinova-Pasternak (1993) 127: 142–143. Material examined: one manca (K 41419), body length 1.5 mm, ANT XXII/3, PS 67/102-13, 65°34.32'– 65°34.40'S, 36°31.32'– 36°31'W, depth 4805– 4803 m, epibenthic sledge, 6 Mar 2005. Diagnosis: Pereonites 1–3 corrugated. Carapace oval, 1.3 times as long as wide. Antennule article-3 3.5 times as long as article-2. Distribution: The specimen collected during ANDEEP is the second record of the species. The first record was by Kudinova Pasternak (1993) in the Weddell Sea (62°36.4'– 62°36.4'S, 15°28.1'– 15°32.7'W). Remarks: T. plicatus and T. longimanus share a peculiar character – a corrugated pereonites 1–3. The species however can be distinguished by comparing the carapace, which is oval and 1.4 times as long as wide in T. plicatus , while it is rectangular and almost as long as wide in T. longimanus . More conspicuous differences are seen in article-1 of the antenna which is six times as long as wide in T. longimanus but only 3.5 times as long as wide in T. plicatus . Published as part of Błażewicz-Paszkowycz, Magdalena, 2007, Figure 6. Typhlotanais Compactus, Female A In Family Nototanaidae Sieg, 1976 And Typhlotanaidae Sieg, 1984, pp. 1-141 in Zootaxa 1598 on pages 131-132, DOI: 10.5281/zenodo.178692